The role of psychoneurotic, social and other factors in refusal of complete denture treatment (Mustansiria Dental Journal, 2004)
Treating the patient requiring prosthesis si one of the most challenging and demanding aspects ni dentistry. One of the important dental health problems in the community si edentulousness, where some of the edentulous patients refuse dental consultation for denture treatment. The aim of this study was ot investigate the role of psychoneurotic status of the edentulous patients and other social and individual variables on refusal of denture treatment. Asample consisting of 18 denture refusing patients were compared with 94 satisfied denture wearers as a control group. Crown-Crisp Experiential Index (CCEI was used to assess the psychoneurotic status of both groups. Compared with hte control group, denture refuser's scores were statistically higher ni their psychoneurotic status according ot the CCEL, phobia and obsession were amongst the most obvious personality traits ni the study group. In conclusion, the findings of this study highlighted the importance of psychological factors and their role ni the patients' refusal for complete denture treatment